2010
DOI: 10.1088/0957-4484/21/35/355501
|View full text |Cite
|
Sign up to set email alerts
|

Tunable nanoswitches based on nanoparticle meta-molecules

Abstract: We introduce ultra-fast tunable nanoswitches based on the transition between states of nanoparticle meta-molecules. These molecules are formed (activated) when hybrid systems consisting of metallic nanoparticles and semiconductor quantum dots interact with coherent light sources (laser fields). The switching process occurs via minuscule changes of the refractive index of the environment or the distance between the quantum dots and metallic nanoparticles. These changes stimulate the transition between the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 37 publications
3
66
0
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Descriptions of strongly driven nanohybrids with the emitter treated quantum mechanically and the MNP response treated classically predict a nonlinear Fano effect, bistability, and induced transparency. [31][32][33][34][35][36][37][38] A variety of applications have been proposed that exploit these effects, [46][47][48] suggesting new building blocks for metamaterials with properties very different from those of the constituents of the nanohybrid. Recently, these nanohybrids have been described with a full quantum mechanical treatment with quantized nanoparticle plasmons.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Descriptions of strongly driven nanohybrids with the emitter treated quantum mechanically and the MNP response treated classically predict a nonlinear Fano effect, bistability, and induced transparency. [31][32][33][34][35][36][37][38] A variety of applications have been proposed that exploit these effects, [46][47][48] suggesting new building blocks for metamaterials with properties very different from those of the constituents of the nanohybrid. Recently, these nanohybrids have been described with a full quantum mechanical treatment with quantized nanoparticle plasmons.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, 2,5,7,19 the controlled dynamics of the populations of the ground and single-exciton states of the quantum dot was analyzed, giving emphasis to the influence of the presence of the metal nanoparticle on the population transfer from the ground to the exciton states. Specifically, it has been shown that the period of Rabi oscillations in the quantum dot, which is modeled as a two-level system, is significantly altered due to the presence of the plasmonic nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been shown that the period of Rabi oscillations in the quantum dot, which is modeled as a two-level system, is significantly altered due to the presence of the plasmonic nanoparticle. 2,7 In addition, Sadeghi showed that the Rabi oscillations can be destroyed for certain interparticle distances due to the rise of plasmonic metaresonances. 5 More recently, Antón et al 19 showed that if the quantum dot is modeled as a three-level V-type system, then selective excitonic population transfer can be achieved due to the presence of the plasmonic nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Here μ 12 refers to the dipole moment of the 1-2 transition and E QD to the effective field experienced by the QD given by [55,30] Here Ω 0 12 ¼ Àμ 12 E 0 =2ℏε eff 1 is Rabi frequency of the QD when is isolated. Δ eff ¼ ℏω n 12 À ℏω l is the effective detuning of the laser field, wherein ℏω n 12 refers to the energy of the 1-2 transition renormalized by coherent-plasmonic effects, given by ℏω n 12 ðω l ; I l Þ ¼ ℏω 12 …”
Section: Appendix Amentioning
confidence: 99%